2019
DOI: 10.1504/ijenm.2019.098107
|View full text |Cite
|
Sign up to set email alerts
|

A simulated annealing for the cell formation problem with ratio level data

Abstract: In this paper, the cell formation problem is considered with ratio level data with an objective of minimising the cell load variation. The attempt has been made to propose a simulated annealing (SA) based on the perturbation scheme as random insertion perturbation scheme (RIPS). The ratio level data is distinguished by utilising the workload information gathered from process times, production quantity of parts and also from the capacity of the machines. A modified grouping efficiency (MGE) is used to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Dmytryshyn et al [27] suggested a novel modeling approach for solving the cell-formation problem. Kamalakannan et al [28] developed a simulated annealing algorithm for solving CFP with ratio level data. Shashikumar et al [29] determined the solution for CFP using a heuristics approach.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…Dmytryshyn et al [27] suggested a novel modeling approach for solving the cell-formation problem. Kamalakannan et al [28] developed a simulated annealing algorithm for solving CFP with ratio level data. Shashikumar et al [29] determined the solution for CFP using a heuristics approach.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…In cell formation literature, besides exact methods, many meta-heuristic techniques have been used. In some studies, Particle Swarm Optimization (PSO) [13,14], Bacteria Foraging Algorithm (BFA) [15], Genetic Algorithm (GA) [11,16], Simulated Annealing (SA) [17,18] techniques were used. In addition, some hybrid [19] and stochastic approaches [20,21] are also presented to solve the cell formation problem.…”
Section: Introductionmentioning
confidence: 99%